Applying Practice Rehearsal Pairs: Improving Students’ Speaking Skill Viewed From Motivation - Mega, Iful Rahmawati (ETERNAL (English Teaching Journal), 2019)
This article refers to an experimental research about the effectiveness of Practice Rehearsal Pairs Method to teach speaking at TOEFL Training Class of Language Laboratory in STKIP Muhammadiyah Bangka Belitung. The population of this research is the university students who took TOEFL Training Class of Language Laboratory in STKIP Muhammadiyah Bangka Belitung. The sample of this research consists of two classes; class A was used as the experimental group treated by using Practice Rehearsal Pairs, and class B as the control group treated by using lecture method, each class consists of 30 students, so the total sample is 60 students. The sampling technique used is purposive sampling. The instruments used to collect the data are students? motivation questionnaire and speaking skill test. The data were analyzed by using multifactor analysis of variance (ANOVA 2X2) and Tukey test. Based on the results of the analysis, the findings of this research are: (1) Practice Rehearsal Pairs is more effective than lecture method to teach speaking; (2) the students with high level of motivation have better speaking skill than those with low level of motivation; and (3) there is an interaction between teaching methods and students? level of motivation to teach speaking. Based on the above findings, it can be concluded that Practice Rehearsal Pairs is an effective method to teach speaking for the university students who took TOEFL Training Class of Language Laboratory in STKIP Muhammadiyah Bangka Belitung?. The effectiveness of the method is influenced by the students? level of motivation.